Mapping of Automobile Dealership Outlets in Skopje - Sasho Nikudinoski, Andreja Naumoski; Naumoski, Andreja; Jovanovska M, Elena (Ss. Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2020)
The purpose of this project is to provide an easier visual access to most of the automobile dealership outlets in Skopje. All car dealership outlets in Macedonia have websites that give detailed information, however sometimes information is not frequently updated. This project will allow people who search for a new car to look at their contact details, address, rating information, opening hours and website info more easily using the visual benefits of ArcGIS. The above data is marked and shown on a geographical map, through a simple overview with visually tagged symbols for each automobile dealership outlet.
Keywords: car, automobile dealership outlets, customers, ArcGIS, interpolation